KOMUNIKASI PERSUASIF DALAM MENINGKATKAN LITERASI DAN NUMERASI DI DAERAH 3T (TERTINGGAL, TERDEPAN, TERLUAR) - ., Hafzotillah; Martha, Layung Paramesti; Nugroho, David Rizar (Universitas Pakuan, 2025)
Communication is a social event, an event that occurs when someone relates to others either face to face or using media as a means of communication. In order to understand the condition of an individual, the ability to communicate persuasively is needed. Lecturers and students observe the condition of the target school and create a literacy and numeracy program that will be implemented in the assigned school. The implementation of the program that has been planned since the beginning of the assignment cannot be separated from persuasive communication in implementing the program. Field supervisors and students need persuasive communication techniques so that the programs that have been released in the assigned school, literacy and numeracy in the modern era, are very easy to apply in the surrounding environment with the help of technology from several planned programs. This study aims to analyze the persuasive communication techniques used by field supervisors and students in the Kampus Mengajar program to improve literacy and numeracy in the 3T area. Using a qualitative descriptive approach, the study was conducted through interviews, FGDs, and observations of lecturers and students at Pakuan University and students at the target school. The results showed that the five persuasive communication techniques used included association, integration, reward, arrangement, and red-herring techniques. Each technique has its own challenges and effectiveness in practice in the field. Communication barriers were identified in the form of technical (facilities) and behavior (lack of student learning motivation). This study concluded that the use of persuasive communication techniques can significantly increase student participation in literacy and numeracy activities, as long as it is supported by appropriate and contextual implementation strategies.